2005
DOI: 10.1074/jbc.m410057200
|View full text |Cite
|
Sign up to set email alerts
|

PYPAF3, a PYRIN-containing APAF-1-like Protein, Is a Feedback Regulator of Caspase-1-dependent Interleukin-1β Secretion

Abstract: PYPAF3 is a member of the PYRIN-containing apoptotic protease-activating factor-1-like proteins (PYPAFs, also called NALPs). Among the members of this family, PYPAF1, PYPAF5, PYPAF7, and NALP1 have been shown to induce caspase-1-dependent interleukin-1␤ secretion and NF-B activation in the presence of the adaptor molecule ASC. On the other hand, we recently discovered that PYNOD, another member of this family, is a suppressor of these responses. Here, we show that PYPAF3 is the second member that inhibits casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 18 publications
3
109
2
Order By: Relevance
“…Previous studies showed that NLRP2 is broadly expressed in tissues and tumor cell lines (6,15). In this study, we report that NLRP2 is up-regulated during differentiation of hemopoietic and mesenchymal progenitors.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies showed that NLRP2 is broadly expressed in tissues and tumor cell lines (6,15). In this study, we report that NLRP2 is up-regulated during differentiation of hemopoietic and mesenchymal progenitors.…”
supporting
confidence: 53%
“…Initial studies showed that NLRP2 is widely expressed in tissues and tumor cell lines (6,15). However, the expression of NLRP2 in progenitor cells and its regulation during differentiation of these progenitors is not known.…”
Section: The Expression Of Nlrp2 Is Up-regulated During Differentiatimentioning
confidence: 99%
“…Similar to PYAF2, PYPAF3 is broadly expressed and induced by LPS or proinflammatory cytokines [29]. However, in contrast to PYPAF2, PYPAF3 has no measured effect on NF-κB activation.…”
Section: Other Negative Regulatory Clr Proteinsmentioning
confidence: 98%
“…PYPAF2 is expressed more broadly than CLR16.2 or Monarch-1 and mRNA can be detected in many different cell types and tissues, including non-hematopoietic cells [19,29]. In addition, distinct from Monarch-1 and CLR16.2, PYPAF2 expression is induced following treatment of cells with LPS or proinflammatory cytokines.…”
Section: Other Negative Regulatory Clr Proteinsmentioning
confidence: 99%
“…92,93 Mutations in NLRP7 have mainly been Genetics of the inflammasomes in human pathologies C Conforti-Andreoni et al 140 associated with aberrant development of the reproductive tract, such as endometrial cancer tissues and familial recurrent hydatidiform moles. 94 Mutations in genes encoding pyrin and proline-serine-threonine phosphatase-interacting protein 1 are associated with two autoinflammatory diseases with hereditary periodic fever syndrome-like symptoms: familial mediterranean fever and pyogenic arthritis pyoderma gangrenosum and acne syndrome, respectively.…”
Section: Genetics Of the Inflammasomes In Human Pathologiesmentioning
confidence: 99%